Alpine Ski - Melzi, S.; Belloni, E.; Sabbioni, E. (The engineering approach to winter sports, 2016)
The purpose of this chapter is to provide an overview of the state of the art about the scientific approach to Alpine Ski. It is common to find manuals with rules of thumbs for the skiers suggested by coaches with respect to a more technical and scientific-oriented publications. Technological and safety aspects are presented in the equipment section: focusing on the helmet, the suit, the boots and the skies, that is the most relevant part of the outfit, technological innovations from the point of view of safety, performances and ergonomics are tackled. A section is then dedicated to the experiments conducted both in open air and in wind tunnel. Different systems will be presented to obtain the desired quantities: the (3D) kinetics of a skier, the ground forces, the aerodynamic contribution, and a comparative analysis between skiing techniques and their performances. Finally, there will be presented (multibody) models for the motion of the skiers, and considerations about trajectory, style, velocity will be made. The task is not so straightforward because of the complexity of the motion and the high number of parameters involved in. Further, a sort of "local" optimization (referred to a specific section of the track) is not sufficient, but the study must be performed on the whole track length to get meaningful results.